The function of interactive techniques English communication skills are important for math students. - Dr. Shatarupa Sing,; Dr. Anil Kumar,; Dr. Bhattachara sharma, (Al-Qanṭara, 2022)
The importance of teaching English communication for engineering students discussed in the article. The world is developing in field of science and technology. Scientific inventions in Germany, France, and Russia cannot reach India through any language other than English. Therefore, a scientific invention in Germany or Russia will have become outdated and old by the time it reaches to Indian scientists through translation.The world is developing in field of science and technology. Scientific inventions in Germany, France, and Russia cannot reach India through any language other than English. Therefore, a scientific invention in Germany or Russia will have become outdated and old by the time it reaches to Indian scientists through translation.